2020
DOI: 10.3390/app10124064
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simulation Model for HMT of a 50 kW Class Agricultural Tractor

Abstract: This study was conducted to develop a simulation model of a 50 kW class hydro mechanical transmission (HMT) tractor and to verify the model by comparing the measured and simulated data, including the axle torque, rotational speed, and power transmission efficiency. The platform of the HMT was composed of the engine, hydrostatic unit (HSU), compound planetary gear, range shift, spiral bevel gear, and final reduction gear. The HMT had three gear stages and a maximum forward speed of 40 km/h. To evaluate the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The theoretical analysis results are consistent with the measured results in the test in terms of the change trend, with small errors. We evaluated the closeness degree of the theoretical characteristics to the measured characteristics using Equations ( 4) and (5). The results show that the coefficient of determination 2 R was 0.92, and the mean absolute percentage error MAPE was 12.56%.…”
Section: Results Of the Test Of The Tractor Hst Adjustable Speed Characteristics And Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical analysis results are consistent with the measured results in the test in terms of the change trend, with small errors. We evaluated the closeness degree of the theoretical characteristics to the measured characteristics using Equations ( 4) and (5). The results show that the coefficient of determination 2 R was 0.92, and the mean absolute percentage error MAPE was 12.56%.…”
Section: Results Of the Test Of The Tractor Hst Adjustable Speed Characteristics And Analysismentioning
confidence: 99%
“…With the continuous development of agricultural modernization and intelligence levels, studies on the techniques of agricultural machinery, such as tractors, are increasingly improved [1][2][3][4][5][6]. Tractors generally work in the conditions of severe environment and variable load.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several researchers proved the reliability of the simulation method based on comfortability, easier, and convenience. The simulation method, which has also been reliable to conduct the performance, design, estimation, and evaluation [35] of the agricultural machinery, reduce labor cost and time-consuming instead of field experiment [36]. The results revealed that the PTO dynamometer can easily control the engine load to estimate fuel consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced technologies such as autonomous, artificial intelligence are applying in the agricultural tractors considering driving comfort, working efficiency, and precision farming [ 1 ]. To confirm the users’ flexibility, precise work, and maximum available power in all conditions during operations, several researchers and manufacturers are developing numerous powertrain system that has included the manual transmission (MT), automatic transmission (AT), dual-clutch transmission (DCT), continuously variable transmission (CVT), and power-shift transmission (PST) for agricultural tractors [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HST (Hydrostatic Transmission) has a low efficiency of less than 70% and comparatively costly [ 2 ]. In the case of HMT (Hydro Mechanical Transmission), the overall efficiency is approximately 80~85% [ 2 , 7 ], and smoothly transmits the power, which applies to the high-power vehicles. Therefore, a PST model was proposed in this study.…”
Section: Introductionmentioning
confidence: 99%